Factors Causing Mis Functional Teacher Guidance Counseling in Schools - Eka Lestari (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to find and analyze the causes of dysfunctional counseling guidance in schools. If this problem is not addressed then the task of guidance teachers and counseling as someone who helps learners in fulfilling the task of development can not be implemented. This will also affect the quality of students in the future not only that this error also has an impact on the professionalism of counseling guidance teachers as a counselor who guides and helps students in maximizing their learning outcomes. The research method used in this study uses descriptive qualitative to provide an overview of the things that have been known and unknown from a particular phenomenon. The results of this study found several factors that cause miss functional guidance teachers in schools, namely: lack of understanding of stakeholders to the duties and functions of counseling guidance teachers, school management that does not facilitate BK teachers, the proportion of counseling guidance in the school curriculum, the professionalism of counseling guidance teachers themselves and differences in background and culture.